Normalization Through the Visual: How International Media Depicted the Abraham Accords - Salama, Mohamed (AUC Knowledge Fountain, 2021)
This study is concerned with understanding the political dimensions of the visual coverage of the Abraham Accords and the shift that might have occurred in the visual portrayal of the Arab-Israeli conflict as a result of that agreement. The study offers quantitative and qualitative contributions to examine how international news websites on the Google News platform used photographs to draw on and contribute to the narrative of Arab-Israeli relations in the wake of the Accords. By establishing operational definitions for positive, negative, anti-normalization, and pro-normalization visual frames, and exploring the use of the emphasis framing device, this study content analyzed 413 photographs in efforts to evaluate the international media’s visual portrayal of the Abraham Accords. The results of the visual framing analysis show that despite the cultural and editorial differences, the vast majority of photographs presented distinctly positive and pro-normalization frames while simultaneously de-emphasized negative frames. As a result, this visual coverage did not widen, but actually narrowed the coverage of the Accords. The study further applied semiotic analysis to investigate whether the visual frames and messages contributed to a broader understanding of the Abraham Accords. The findings suggest that news outlets are not simply carriers of news; rather, they have a substantial influence on the news events they cover through their publication of photographs and captions, which can anchor meaning for readers. This study further finds that captions can play an essential part in facilitating the decoding process of certain visuals because images are sometimes enriched with great meaning that is less easily accessed by those who lack a certain degree of cultural and contextual understanding.